2012
DOI: 10.1542/peds.2011-0104
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Sunburn and Sun Behavior Patterns During Adolescence

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Childhood UV light exposures, specifically sunburns, have been shown to be associated with melanoma development later in life.WHAT THIS STUDY ADDS: To date, most studies in this age group have been cross sectional in nature. This is the first prospective study of sunburn and sun behaviors in this age group. abstract OBJECTIVES: Early childhood UV light radiation (UVR) exposures have been shown to be associated with melanoma development later in life. The objective of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 30 publications
4
40
1
2
Order By: Relevance
“…1821 We previously reported on the stability and volatility of nevi in this cohort, finding a median increase of two new back nevi over a three year period from the fifth to eighth grade, with 75% of participants having one new back nevus. 22 Previous analyses also suggested that factors such as high baseline nevus count at age 11, globular nevi dermoscopic pattern, and sunburn were associated with an increase in total nevus count by age 14.…”
Section: Introductionmentioning
confidence: 62%
“…1821 We previously reported on the stability and volatility of nevi in this cohort, finding a median increase of two new back nevi over a three year period from the fifth to eighth grade, with 75% of participants having one new back nevus. 22 Previous analyses also suggested that factors such as high baseline nevus count at age 11, globular nevi dermoscopic pattern, and sunburn were associated with an increase in total nevus count by age 14.…”
Section: Introductionmentioning
confidence: 62%
“…Framingham, Massachusetts conducted a population-based study showing that 55% of children reported experiencing one or more sunburns during the prior summer and, more alarmingly, only 25% routinely used sunscreen [8]. There is a need to integrate sunscreen use into children's daily routines to reduce their risk of developing skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They are the most common type of burn, with at least 50% of children experiencing a sunburn before the age of 11 years. 15 Sunburns will appear similar to thermal burns and can range from painless erythema to painful erythema with edema and bullae, appearing in sunexposed areas only. conclusively been shown to be superior.…”
Section: Treating Chemical Burnsmentioning
confidence: 99%